Historical context and educations acts at the Araraquara Science Center: 30 yaers of a university museum in the countryside of São Paulo - Silveira, Camila; Maruyama, José Antonio (Revista CPC, 2022)
University Museums are institutions of important social function linked to universities, acting in Teaching, Research and Extension. Research on these institutions and their practices can highlight aspects that further the understanding of their particularities in the museum field. This paper analyzes the consolidation of the Araraquara Science Center (CCA) as a University Museum, emphasizing its educational actions. As a qualitative documentary research, it analyzed the museum’s historical documents, such as institutional decrees, newspaper reports, photographs, reports and scientific productions. These data allowed to trace CCA’s historical path, marked by three major phases that indicate the team’s role and commitment, the expansion of its actions, the museum characterization, and the strategies developed to overcome operational obstacles for maintining its activities.